Loyalitas Pelanggan Maxim Bike: Peran Kepercayaan, Harga, dan Kepuasan dalam Perspektif Bisnis Islam - Syahid Amrulloh; Ahmad Zuliansyah; Yeni Susanti (Universitas Muhammadiyah Palembang, 2026)
The rapid development of digital technology has driven innovations in online transportation services that offer convenience, speed, and efficiency, one of which is Maxim Bike. This study aims to analyze the effect of trust, price, and customer satisfaction on customer loyalty among Maxim Bike users in Bandar Lampung City. The research employs a descriptive quantitative method with a sample of 97 respondents. Data were collected through observation, interviews, and questionnaires, and analyzed using SmartPLS 4 with validity, reliability, hypothesis testing, and coefficient of determination (R²). The results indicate that trust and customer satisfaction have a positive and significant effect on customer loyalty, while price has no significant effect. This suggests that customer loyalty is more influenced by the quality of relationships and customer experience than by price factors. Theoretically, this study highlights the importance of trust and satisfaction as key determinants of loyalty in digital service marketing, while also aligning with Islamic business values such as trustworthiness (amanah), honesty, and fairness. Practically, companies are advised to enhance service quality, information transparency, as well as user safety and comfort, while maintaining fair pricing to sustain perceived customer value.